Lupin kernel fiber consumption modifies fecal microbiota in healthy men as determined by rRNA gene fluorescent in situ hybridization - Smith, Stuart C.; Choy, Rachel; Johnson, Stuart K.; Hall, Ramon S.; Wildeboer-Veloo, Alida C.M.; Welling, Gjalt W. (European journal of nutrition, 2006)
Changes in the composition of gastrointestinal microbiota by dietary interventions using pro- and prebiotics provide opportunity for improving health and preventing disease. However, the capacity of lupin kernel fiber (LKFibre), a novel legume-derived food ingredient, to act as a prebiotic and modulate the colonic microbiota in humans needed investigation. The present study aimed to determine the effect of LKFibre on human intestinal microbiota by quantitative fluorescent in situ hybridization (FISH) analysis. A total of 18 free-living healthy males between the ages of 24 and 64 years consumed a control diet and a LKFibre diet (containing an additional 17-30 g/day fiber beyond that of the control-incorporated into daily food items) for 28 days with a 28-day washout period in a single-blind, randomized, crossover dietary intervention design. Fecal samples were collected for 3 days towards the end of each diet and microbial populations analyzed by FISH analysis using 16S rRNA gene-based oligonucleotide probes targeting total and predominant microbial populations. Significantly higher levels of Bifidobacterium spp. (P = 0.001) and significantly lower levels of the clostridia group of C. ramosum, C. spiroforme and C. cocleatum (P = 0.039) were observed on the LKFibre diet compared with the control. No significant differences between the LKFibre and the control diet were observed for total bacteria, Lactobacillus spp., the Eubacterium spp., the C. histolyticum/C. lituseburense group and the Bacteroides-Prevotella group. Ingestion of LKFibre stimulated colonic bifidobacteria growth, which suggests that this dietary fiber may be considered as a prebiotic and may beneficially contribute to colon health.